4x - (9 - 3x) = 8x - 1
4x - 9 + 3x = 8x - 1
7x - 9 = 8x - 1
-9 + 1 = 8x - 7x
-8 = x
x = -8
2007-04-29 13:35:35
·
answer #1
·
answered by skm4usa 3
·
1⤊
0⤋
Honors Math, do not fail me now. the answer is x = -8 First, the parentheses, -(9-3x) this may get replaced to -(9+-3x) then to -9+3x now you've... 4x+-9+3x=8x-a million Subtract 4x from each and each and every section... , replace 4x-a million to 4x+-a million Now that's... -9+3x=4x+-a million upload a million to each and each and every section... -8+3x=4x subtract 3 x from each and each and every section and now you get -8=1x or -8=x -8 is your answer
2016-11-23 15:51:44
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
4x-(9-3x)= 8x-1
4x-9+3x=8x-1
7x-9=8x-1
-8=x
4(-8) - 9 + 3(-8) = 8(-8) -1
-32-9-24 = -64-1
-41-24=-65
-65=-65
Hope this helps!
2007-04-29 13:42:38
·
answer #3
·
answered by allstargurl522 3
·
0⤊
0⤋
4x - (9 - 3x) = 8x - 1
4x - 9 + 3x = 8x - 1
7x - 9 = 8x - 1
7x - 9 - 8x = 8x - 1 - 8x
- x - 9 = - 1
- x - 9 + 9 = - 1 + 9
- x = 8
-1(- x) = - 1(8)
- (- x) = -8
x = - 8
- - - - - - - - - -s-
2007-04-29 13:53:35
·
answer #4
·
answered by SAMUEL D 7
·
0⤊
0⤋
First distribute the minus sign in front of the parenthenses.
4x-9+3x+8x-1
Then combine like terms on each side.
7x-9=8x-1
Then solve for "x."
-8=x
2007-04-29 13:36:30
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
4x-(9-3x)=8x-1
4x-9+3x=8x-1
7x-9=8x-1
-x-9=-1
-x=8
x=-8
Check:
4(-8)-(9-3(-8))=8(-8)-1
-32-(9+24)=-64-1
-32-33=-64-1
-65=-65
2007-04-29 13:36:40
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋